2007
DOI: 10.1002/qua.21394
|View full text |Cite
|
Sign up to set email alerts
|

The influence of molecular structure on the change of the arrhenius factor of gas‐phase elimination of nitric acid from nitroalkanes

Abstract: ABSTRACT:The Arrhenius factor of gas-phase elimination of nitric acid from nitrocompounds was estimated. Asymmetric internal rotation was taken into account. To this end, an appropriate mathematical apparatus was developed. The geometry, transition state, rotation barriers and vibration frequencies were found by the density functional theory method B3LYP/6-31G(d) by means Gaussian 98 program. The influence of the molecular structure on the Arrhenius factor was considered. The reaction barriers were estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…By inclusion of all internal rotations, one gets the kinetic results (log A Int and k Int ). The deviation at the DFT methods from experiment decreases and is less than 0.24 log unit, indicating that the internal rotations practically affect the change of the pre-exponential factor, which was testified to previously by Shamsutdinov et al 61 The k F value is obtained by mutiplying k Int and the Wigner tunneling correction evaluated using the imaginary frequency (1312i, 1292i, and 1356i cm À1 at the B3LYP, B3PW91, and MP2 levels, respectively); the calculated k F (1.29 Â 10 À2 s À1 ) at the B3PW91 level agrees very well with the experimental result of 1.19 Â 10 À2 s À1 . It can be also seen from Table 2 that this reaction, which has a chemical endothermicity (ΔE) of 75À100 kJ/mol, can be identified as a potential source of cooling to increase the fuel heat sink.…”
Section: Cme Mechanismsupporting
confidence: 77%
“…By inclusion of all internal rotations, one gets the kinetic results (log A Int and k Int ). The deviation at the DFT methods from experiment decreases and is less than 0.24 log unit, indicating that the internal rotations practically affect the change of the pre-exponential factor, which was testified to previously by Shamsutdinov et al 61 The k F value is obtained by mutiplying k Int and the Wigner tunneling correction evaluated using the imaginary frequency (1312i, 1292i, and 1356i cm À1 at the B3LYP, B3PW91, and MP2 levels, respectively); the calculated k F (1.29 Â 10 À2 s À1 ) at the B3PW91 level agrees very well with the experimental result of 1.19 Â 10 À2 s À1 . It can be also seen from Table 2 that this reaction, which has a chemical endothermicity (ΔE) of 75À100 kJ/mol, can be identified as a potential source of cooling to increase the fuel heat sink.…”
Section: Cme Mechanismsupporting
confidence: 77%
“…Numerous substances such as transition-metal complexes, Lewis acids, Brønsted acids, bases, and water have been developed to catalyze the Claisen rearrangement and accelerate it [6]. Maruoka et al [27,49] have shown that the reaction rates of the AVE derivatives are increased in the presence of aluminum complexes. The catalyst on the basis of copper (II) complexes was also described [50].…”
Section: Catalytic Effectsmentioning
confidence: 99%
“…Complementary to that, quantummechanical calculations can yield bond distances and other geometric information which give more direct answer, since it mirrors the key characteristic of the critical species involved, rather than arguing over the boundary conditions [19][20][21]. The -----usage of the modern quantum chemistry methods can not only provide geometrical parameters being close to experimental ones but they can correctly forecast the activation parameters of a chemical reaction such as activation energy and reaction enthalpy [22][23][24][25][26][27][28]. Both the new experimental and theoretical approaches allow to break down the multiple interpretations options to one mechanism and one transition state for a given reaction under given conditions.…”
Section: Introductionmentioning
confidence: 99%